2022
DOI: 10.1063/5.0128049
|View full text |Cite
|
Sign up to set email alerts
|

Robust air cavity generation on sacrificial microstructures for sustainable underwater drag reduction

Abstract: Reducing fluid frictional drag at the solid–liquid interface is a promising strategy for improving the hydrodynamic properties of the structure in water, though so far it has remained unattainable without robust air cavities. Herein, we report a durable generation strategy of robust air cavity on the rough microstructured surface, which could achieve stable drag reduction even after 2000th water entry test. It is worth noting that the generation strategy is almost independent of the wear of surface microstruct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Extensive research work has focused on drag reduction and various strategies have been developed to construct an air layer on a structural body’s surface so as to produce significant slip in contact with fluid flow, reducing the shear forces at the boundary and producing drag reduction properties. Vakarelski et al used the Leidenfrost effect to completely encase a metal sphere falling into a liquid in a stable streamlined air cavity, which eliminates contact between the surface of the sphere and liquid, and the drag coefficient of the streamlined sphere-in-cavity structure is approximately 0.02–0.03. Liu et al conducted an experimental study on the drag reduction performance of mixed solutions of polymers and surfactants, and the experimental results showed that the mixed solutions could inhibit the generation of vortices more effectively and improve the drag reduction efficiency . Wang et al investigated the mechanism of microstructured spheres to reduce the critical velocity of air cavity entrainment, analyzed the effect of surface morphology effect on hydrodynamic properties, and further revealed the mechanism of surface morphology effect-induced drag reduction in underwater air cavities by numerical simulation. Liao et al used femtosecond lasers to prepare superhydrophobic glass microchannels with drag-reducing properties, which were able to significantly reduce the flow drag of microfluidics . Zhang et al were inspired by the fine hairs and cilia of living organisms to prepare a hair-like superhydrophobic surface by electrostatic value linting and subsequent surface modification, which has excellent mechanical stability and enables an effective drag reduction effect .…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research work has focused on drag reduction and various strategies have been developed to construct an air layer on a structural body’s surface so as to produce significant slip in contact with fluid flow, reducing the shear forces at the boundary and producing drag reduction properties. Vakarelski et al used the Leidenfrost effect to completely encase a metal sphere falling into a liquid in a stable streamlined air cavity, which eliminates contact between the surface of the sphere and liquid, and the drag coefficient of the streamlined sphere-in-cavity structure is approximately 0.02–0.03. Liu et al conducted an experimental study on the drag reduction performance of mixed solutions of polymers and surfactants, and the experimental results showed that the mixed solutions could inhibit the generation of vortices more effectively and improve the drag reduction efficiency . Wang et al investigated the mechanism of microstructured spheres to reduce the critical velocity of air cavity entrainment, analyzed the effect of surface morphology effect on hydrodynamic properties, and further revealed the mechanism of surface morphology effect-induced drag reduction in underwater air cavities by numerical simulation. Liao et al used femtosecond lasers to prepare superhydrophobic glass microchannels with drag-reducing properties, which were able to significantly reduce the flow drag of microfluidics . Zhang et al were inspired by the fine hairs and cilia of living organisms to prepare a hair-like superhydrophobic surface by electrostatic value linting and subsequent surface modification, which has excellent mechanical stability and enables an effective drag reduction effect .…”
Section: Introductionmentioning
confidence: 99%